(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Thermal properties of torrefied empty fruit bunch biochar were investigated in this study as an alternative to be a renewable energy material for future. Holding temperature range between 200 to 300°C and residence time for 30 to 90 minutes were applied as the factors for the torrefaction process. This study observed the thermal properties of torrefied empty fruit bunch biochar by using thermogravimetric analysis (TGA) to study the thermal decomposition before and after torrefaction process. Thermogravimetric analysis was used in identifying those properties, which is dividing into three stages of dehydration, devolatilizations and decomposition of the torrefied biochar. During the dehydration, the moisture content was removed, meanwhile during the second stage (devolatilizations), the volatile matter was removed along with the removal of hemicellulose, cellulose, and lignin, while on the third stage shows the decompositions of the torrefied biochar to completely degrade.